Regulation of the Limits of Authority of a Notary Undergoing Detention Without Temporary Suspension - Anggie Natasia Theis; Alfons Zakharia; Fathul Laila (Faculty of Law, Merdeka University Surabaya, Indonesia, 2026)
Existing studies on notarial authority in Indonesia, such as analyses of the Law on Notarial Office (UUJN), have addressed general supervisory mechanisms and temporary suspensions but overlook the critical transitional period when a Notary faces detention (e.g., house arrest or city detention) without formal suspension. This gap leaves unresolved tensions between a Notary's persisting administrative authority and factual restrictions on liberty, potentially undermining the independence, objectivity, and validity of authentic deeds core to their role as public officials producing instruments with full evidentiary force. Addressing this novelty, this study analyzes the urgency of regulating limits on a detained Notary's authority who has not yet been temporarily suspended and formulates a regulatory model to ensure legal certainty and public protection. Employing a normative legal method with statutory and conceptual approaches, the research reveals that UUJN and its regulations lack operational boundaries for this scenario: normatively, authority persists, yet factually it cannot be exercised optimally, breeding legal uncertainty. The proposed model innovatively differentiates administrative status from functional eligibility, mandating temporary transfer of authority to a Substitute Notary.